2007
DOI: 10.2478/s11687-007-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

From cestodes to nematodes: 15 years of scientific collaboration between the Parasitological Institute SAS and the Section of Parasitology of the Sapienza University of Rome

Abstract: have had a long term collaboration within several projects, starting with the first visiting fellowships in 1992 in Rome. Since then, the collaboration between the two institutions has continuously developed and has been focused mainly on the systematics of cestodes, starting in particular with the studies on the genetic polymorphism of fish Proteocephalus tapeworms in different host populations examined by enzyme electrophoresis. Some molecular studies have been later carried out on Eubothrium spp. and Echino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…(2003) revealed the occurrence of G7 (pig) strain on our territory. Recent data of D′Ammelio and Šnábel (2007) also report only the occurrence of G7 strain in Slovakia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003) revealed the occurrence of G7 (pig) strain on our territory. Recent data of D′Ammelio and Šnábel (2007) also report only the occurrence of G7 strain in Slovakia.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of cystic material from pigs, cattle and human patients by Turčeková et al (2003) revealed the occurrence of G7 (pig) strain on our territory. Recent data of D¢Ammelio and Šnábel (2007) also report only the occurrence of G7 strain in Slovakia.…”
Section: Introductionmentioning
confidence: 99%